CLOUD SERVICES FOR ORGANIZATION OF STUDENTS' EDUCATION ACTIVITY CONTROL - Olesya M. Abramova (Moscow Polytechnic University, 2016)
The article dwellson thequestions ofa choice and theuse of innovative technologies forcontrol of education activity of futureeconomists when studyingdiscipline «Linear algebra». The article discuss the methodical possibilities of cloud services that functionally are the most suitable for the organization of educational activity control in the modern educational environment. The list ofthe most applicable cloud services for the realization of new forms and methods of student training, with the indication of their advantages and is provided.